Recent designer surfactants for catalysis in water. Issue 14 (30th June 2020) - Lorenzetto, Tommaso; Berton, Giacomo; Fabris, Fabrizio; Scarso, Alessandro
Abstract : Recent development of new designer surfactants further spurs the development of micellar catalysis in water for chemical transformations and catalysis, providing reliable alternatives to the employment of organic solvents. Abstract : The use of water as a solvent for chemical transformations and catalysis is not only a counter-intuitive original approach with respect to catalysis in traditional media, but thanks to micellar catalysis and the recent development of new designer surfactants, it is becoming an important real benchtop alternative to the employment of organic solvents. Micellar catalysis has received new focus thanks to the recent introduction of the so-called designer surfactants by the group of Lipshutz as surfactants specifically designed and tested for catalysis in water. In particular, the advent of the benchmark TPGS-750-M has really revolutionized chemical synthesis and catalysis in aqueous media, leading also to important positive outcomes suitable for industrial scale applications. The present contribution covers the preparation and the applications in chemical transformations and catalysis of very recent new designer surfactants. These are readily available and economic amphiphiles, mostly prepared from renewable resources, that are specifically designed and tested for catalytic reactions in water. In particular, different neutral designer surfactants are covered and critically classified and discussed.